1990
DOI: 10.1111/j.1752-1688.1990.tb01433.x
|View full text |Cite
|
Sign up to set email alerts
|

THE POTENTIAL EFFECTS OF GLOBAL WARMING ON THE PRIMARY PRODUCTIVITY OF A SUBALPINE LAKE1

Abstract: Atmospheric scientists have predicted that large-scale climatic changes will result from increasing levels of tropospheric CO2. We have investigated the potential effects of climate change on the primary productivity of Castle Lake, a mountain lake in Northern California. Annual algal productivity was modeled empirically using 25 years of limnological data in order to establish predictive relationships between productivity and the climatic variables of accumulated snow depth and precipitation. The outputs of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…While the depth of the euphotic zone, and the extent of the zone inhabited by deep algal blooms increased, there was no corresponding climate-related change in either total area or subthermocline rates of production (Schindler et al, 1996a). In contrast, Byron and Goldman (1990) found that climatic warming caused increases in both phytoplankton production and standing crop in Castle Lake.…”
Section: Changing Climate and Aquatic Organismsmentioning
confidence: 74%
“…While the depth of the euphotic zone, and the extent of the zone inhabited by deep algal blooms increased, there was no corresponding climate-related change in either total area or subthermocline rates of production (Schindler et al, 1996a). In contrast, Byron and Goldman (1990) found that climatic warming caused increases in both phytoplankton production and standing crop in Castle Lake.…”
Section: Changing Climate and Aquatic Organismsmentioning
confidence: 74%
“…However, annual algal abundance in mountain lakes and ponds can be positively correlated with climate-driven events, such as warmer and longer ice-free growing seasons (Byron and Goldman 1990;Sommaruga-Wögrath et al 1997). Culturing experiments show that warming can enhance gross primary production as an increase of 10ЊC doubles enzymatic rates (Davison 1991).…”
mentioning
confidence: 99%
“…Primary production is also important because it consumes CO 2 and thus sequesters some of this greenhouse gas and plant nutrients, especially at the scale of the world's oceans. Despite the tremendous interest in this topic, there is limited empirical evidence indicating how lake primary productivity might respond to global warming (Carpenter et al 1992;Magnuson et al 1997; however, see Byron and Goldman 1990;Findlay et al 2001). Because primary production provides the energetic basis for almost all ecosystems, it is essential to know how interannual variability of primary productivity is controlled by the underlying mechanisms that drive this process at longer time scales.…”
mentioning
confidence: 99%